Влияние курения на организм спортсмена - Абдуллаев, Алтай Карам-Оглы; Абдуллаєв, Алтай Карам-Огли; Abdullaev, Altai; Ребар, І. (My University, 2017)
RU: В данной статье рассмотрены проблема, актуальность, задачи негативного влияния курения на физические и психическое здоровье спортсмена. Также проанализирована специальная литература. Рассмотрены последствия, к которым приводит употребление табака. Приведен список болезней, которые возникают при употреблении табака. Описан состав сигарет. Описано влияние курения не только на самого курильщика, но и на окружающих его людей. Рассмотрена роль спорта в борьбе с курением. UK: У даній статті розглянуті проблема, актуальність, задачі негативного впливу куріння на фізичне і психічне здоров'я спортсмена. Також проаналізована спеціальна література. Розглянуто наслідки, до яких призводить вживання тютюну. Приведений список хвороб, які виникають при вживанні тютюну. Описано склад сигарет. Описано вплив куріння не тільки на самого курця, але і на оточуючих його людей. Розглянуто роль спорту у боротьбі з курінням. EN: One of the reasons that contribute to counter the habit of smoking is a widespread perception that tobacco increases efficiency. To get rid of this habit is not enough willpower and often knowledge of what products are harmful smoking person inhales and what happens in the body during smoking. Smoker’s athletes are at increased risk of injury and bruises and fractures heal more slowly. Official science and medicine proved that smoking doubles the risk of coronary heart disease. This article describes the problem, the urgency, the problem of negative effects of smoking on physical and mental health of the athlete by analyzed the special literature. We consider the consequences that tobacco use causes. Among smokers and non-smoking section of the students wrestling endurance has been performed research of speed, responsiveness using the standards of general physical training. Detailed a list of diseases that occur during the use of tobacco. Describes the composition of cigarettes. Describes the effects of smoking not only the smoker but also the people around him. Examined the role of sport in the fight against smoking. The results can be used for trainings, seminars, classroom hours devoted to a healthy lifestyle, in the training process in the preparation of athletes at different levels. 1. The results of the study can be used to promote among students the harm that smoking is causing young people, including athletes. 2. Develop measures and ways of overcoming tobacco dependence in athletes. 3. Develop a program of "mobile laboratories" for treatment of tobacco dependence.
Вплив тютюнопаління на організм спортсмена
Effects of the smoking occurred on the athlete’s body
Keywords: спорт; курение; угарный газ; никотин; смола; мелатонин; мышечная масса; куріння; чадний газ; нікотин; мелатонін; м'язова маса; sports; smoking; carbon monoxide; nicotine; tar; melatonin; muscle mass